Consumer acceptance of using a digital technology to manage postpartum depression - Tang, Jian Jenny; Malladi, Indira; Covington, Melva T.; Ng, Eliza; Dixit, Shailja; Shankar, Sid; Kachnowski, Stan (Frontiers in Global Women's Health, 2022)
The goal of the study was to evaluate the end user experience using the Stella-tTM app for 2 weeks to support the treatment of their postpartum depression (PPD). A total of 14 participants completed the study and their experiences are reported in this publication. Participants reported that Stella-t is an acceptable, highly usable, and practical mobile tool to use weekly for the management of their PPD. More research is warranted to evaluate the benefit of digital behavior health interventions, especially in patient populations where mental health care may be limited or harder to access.